Application of evolutionary algorithms to the definition of the optimal twin-screw extruder configuration for starch cationization - Teixeira, Cristina (2011)
The Twin Screw Configuration Problem (TSCP) involves defining the location of a set of pre-defined screw elements of a co-rotating twin-screw extruder configuration in order to optimize different, often conflicting, objectives. A multi-objective optimization methodology based on Evolutionary Algorithms was developed and applied to solve the TSCP. This methodology is used in starch cationization case studies, involving different screw elements and screw lengths. The results obtained, taking into consideration various conflicting objectives, such as minimizing the specific mechanical energy and maximizing output and reaction efficiency, have physical meaning and thus validate the methodology.